S Strategi Pengembangan Fasilitas Sarana dan Prasarana Pantai Tuing Indah Kabupaten Bangka Provinsi Kepulauan Bangka Belitung: Strategi Pengembangan Fasilitas Sarana dan Prasarana Pantai Tuing Indah Kabupaten Bangka Provinsi Kepulauan Bangka Belitung - gresella, jessica; Pratiwi, Fika Dewi; Aisyah, Siti (Akuatik: Jurnal Sumberdaya Perairan, 2023)
Sustainable tourism defined as tourism that takes full account of economic, social and environmental impacts, this is a factor that supports the use of local resources at Tuing Indah Beach, Mapur Village to make the future of tourism more viable and provide economic and social benefits for community. This research aims to analyze what internal and external factors can influence the development of facilities and infrastructure at Tuing Indah Beach and analyze development strategies based on SWOT analysis at Tuing Indah Beach. Thebeach infrastructure development strategy uses an aggressive strategy, while the beach infrastructure development strategy uses a turn around strategy. This is based on calculations from the analysis results which show that tourism facility development activities are at the coordinate point (0.2063 ; 0.3475), namely quadrant I with the prioritized development strategy being (SO) Strength Opportunity, namely development by utilizing existing strengths and optimizing existing opportunities. Meanwhile, the development of tourism infrastructure facilities is at the coordinate point (-0.2078 ; 0.2111), namely quadrant II with the prioritized development strategy being (WO) Weaknees Opportunity, namely development by minimizing weaknesses so that we can take advantage of existing opportunities.